Myths and rituals among the Babaylan of Tubungan, Iloilo. - Cadiz, Fel Ceasar Tubelleza
This paper is an exploratory study on myths, an important genre in folk literature, and their relation to binabaylan in Tubungan. Specifically it aims to identify and discuss myths found in the locale; To describe specific agricultural rituals, beliefs, and practices; To analyze the relationship between agricultural myths and rituals; and lastly, to describe and analyze the function(s) of rituals and myths in the context of binabaylan in Tubungan., The study discusses six myths namely: Apik and Manampunay, Pinihakang Daraga, the Datu and the Panaet, the seven Bacam jars and the Panaitan, the origin of rice, corn and beans and the origin of rice varieties. These myths are then analyzed to reveal their importance in the binabaylan symbolism and ideology. The study also discusses seven agricultural rituals namely: paminhi, patubong, panaet, panudlak, tuos, tagurabong, and panguyang. Each ritual is discussed including their accompanying hurobaton (ritual-chant), taboos observed and food being offered. After examining the relationship between the agricultural rituals and the myths, the paper concludes that not all myths have corresponding rituals. Certain rituals have retained their mythic explanation, some have not. Myths and rituals reveal an orientation about the world and of of reality. Through the recitation of myths in rituals, people learn not only to adjust themselves within the society to which they are born, but also to match their personal pains and conflicts to those of the heroes narrated in these stories. In these ways, they gain guidance and, eventually, wisdom.